Multiple nitric oxide synthase systems in adult rat thymus revealed using NADPH diaphorase histochemistry. - Downing, J E (1994)
Nitric oxide (NO) has become recognized as a multifunctional mediator, with roles in vascular physiology, neurotransmission and non-specific immune defense. The histochemical marker associated with the neural and endothelial form of NO synthase (NOS), reduced nicotinamide adenine dinucleotide diaphorase (NADPHd), has enabled the indirect localization of potential sites of NO production. Innervation of the thymus and its immunological functions made this tissue a candidate for utilization of various NO systems. In the present study on adult rat thymus, multiple cellular sites expressing NADPHd activity, thereby implicated as sites of NOS activity, have been identified using morphological criteria alone: blood vessel endothelium, dendritic cells, deep cortical or medullary stromal cells, intrinsic neuron-like profiles, granulocytes (possibly neutrophils) and fat cells. In addition, the availability to the thymic microenvironment of another form of NOS in macrophages, which is not stained by the diaphorase technique, was supported by the observation of these cells at corticomedullary and cortical locations. These results indicate that a wide variety of possible immunomodulatory roles can be expected for NO in the thymus including the induction of tolerance, major histocompatibility complex (MHC) restriction, lymphocyte trafficking and regulation of thymic endocrine output.